Non-stoichiometric zinc ferrite nanostructures: Dielectric, magnetic, optical and photoelectrochemical properties. (September 2021) - Salman, Muhammad; Khan, Majid; Saleem, Sumaiya; Ali, Salman; Hussain, Fayaz; Muhammad, Raz; Khesro, Amir; Abdullah,; Ling, Yihan
Abstract: Spinel zinc ferrite nanostructures possess incredible dielectric and magnetic properties due to the presence of oxygen vacancies, cation distribution and surface spin disorder. However, the mechanism behind the photoelectrochemical properties is seldomly investigated. Herein, we report the influence of zinc non-stoichiometry on the optical, dielectric, magnetic and photoelectrochemical properties of zinc ferrite by preparing polyvinylpyrrolidone (PVP) coated and uncoated Znx Fe2 O4±δ (x = 1, 0.98 and 1.02) nanostructures synthesized via the hydrothermal method. X-ray diffraction showed the formation of a single-phase spinel structure of all the samples. FTIR spectroscopy confirmed the formation of the metal oxide with two of its fingerprint vibrational bands detected near 550 cm −1 and 400 cm −1 . Moreover, a decrease in bandgap (Eg ) and the saturation magnetization values were observed for Zn-deficient samples. The dielectric constant and dielectric tangent loss measurement showed similar dielectric behavior for all the ZnFe2 O4 samples. The variation in dielectric permittivity and dielectric tangent loss, with the concentration of zinc, were found to be in good agreement with Koop's phenomenological theory of dielectric dispersion. The photoelectrochemical (PEC) characterization of the prepared samples was investigated for hydrogen production under visible light irradiation. It was found that the 2% Zn-deficient electrode (higher photocurrent density, −0.336 V flat-band potential and 1575 Ohm charge transfer resistance) increased PEC water oxidation activity compared to pure and excess ZnFe2 O4 electrodes. The deficiency of Zn increased the majority carrier concentration and surface defects, which in turn improved the surface charge separation efficiencies. The results give a new perspective on the importance of zinc ferrite as a catalyst to synthesize photoelectrodes for efficient solar energy conversion devices. Graphical Abstract: ga1 Highlights: Non-Stoichiometric ZnFe2 O4 nanostructures were prepared by the hydrothermal method. The stoichiometry is changed by a 2% increase and decrease of Zn contents. By increasing Zn concentration, the optical band gap of zinc ferrite reduces. The maximum saturation magnetization value founded for the 2% Zn excess samples. Zn-deficient samples show lower Vfb and RCT, and higher photocurrent density.